(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The process of forming patriotic features in the child’s mentality and the child’s ability to domature and responsible acts have been studied in the article. The author has come to the conclusion that exactly the models of above-mentioned acts should be used for educating the modern generation.